Assessment of oligofructose and glycerol supplementation on glass transition temperature and quality of frozen yogurt. Issue 11 (5th August 2022) - Muzammil, Hafiz Shehzad; Junaid, Muhammad; Sameen, Aysha; Syed, Qamar Abbas; Shukat, Rizwan; Aadil, Rana Muhammad
Abstract: Frozen yogurt is one of the most common types of dairy functional food. It has the characteristics of both yogurt and ice cream. The present study was planned to see the effects of oligofructose and glycerol supplementation on glass transition temperature and other structural properties of probiotic frozen yogurt. Frozen yogurt was prepared with probiotics ( Lactobacillus acidophilus and Bifidobacterium lactis ) and yogurt starter cultures ( Streptococcus thermophilus and Lactobacillus bulgaricus ). Furthermore, in frozen yogurt mixture oligofructose (2%, 4%, and 6%), and glycerol (1%, 2%, 3%, and 4%) were supplemented. The results have shown that oligofructose supplementations have increased the total solids, overrun, and stickiness, while decreased the hardness significantly ( p  < .05). Oligofructose also has shown a non‐significant effect on melting rate, air cell size, ice crystal size ( p  > .05). However, the glycerol supplementations have increased the melting rate while decreased the glass transition temperature significantly ( p  < .05). The oligofructose and glycerol can be used to improve the textural properties of frozen yogurt. Novelty impact statement: The probiotic frozen yogurt with different ingredients and combinations of prebiotics (fructooligosaccharides, oligofructose, inulin, etc.) were prepared and its quality was analyzed in various previous studies but the combined effect of prebiotic with cryoprotectant (glycerol) was not investigated so far. So, in the current study, the oligofructose and glycerol's effect on frozen yogurt texture, melting rate, air cell size, ice crystal size, and on glass transition temperature were evaluated and the results are discussed in this manuscript.